Evaluation of Ultrasonic Nonlinear Characteristics in Heat-Treated Aluminum Alloy (Al-Mg-Si-Cu) - JongBeom Kim; Kyung-Young Jhang (Advances in Materials Science and Engineering)
The nonlinear ultrasonic technique has been known to be more sensitive to minute variation of elastic properties in material than the conventional linear ultrasonic method. In this study, the ultrasonic nonlinear characteristics in the heat-treated aluminum alloy (Al-Mg-Si-Cu) have been evaluated. For this, the specimens were heat treated for various heating period up to 50 hours at three different heating temperatures: 250°C, 300°C, and 350°C. The ultrasonic nonlinear characteristics of each specimen were evaluated by measuring the ultrasonic nonlinear parameter β from the amplitudes of fundamental and second harmonic frequency components in the transmitted ultrasonic wave. After the ultrasonic test, tensile strengths and elongations were obtained by the tensile test to compare with the parameter β. The heating time showing a peak in the parameter β was identical to that showing critical change in the tensile strength and elongation, and such peak appeared at the earlier heating time in the higher heating temperature. These results suggest that the ultrasonic nonlinear parameter β can be used for monitoring the variations in elastic properties of aluminum alloys according to the heat treatment.